Analisis Kesalahan dalam Penulisan Laporan Penelitian dari Study Tour di SMP dan SMA: Upaya Peningkatan Kualitas Pelaporan - Hasna Mutia Insani; Aviana Zahrotun Nabilah; Ana Listy Fikri Nur Issabil; Sri Sukasih (LPPM Politeknik Pratama, 2023)
Writing is an important skill that everyone must master. Good writing will make it easier for readers to understand the meaning of the article. However, there are still many people who make mistakes in writing, including middle school and high school/vocational school students. This research aims to analyze writing errors in student study tour reports at SMP Negeri 1 Semarang and SMK Cor Jesu Malang. This research uses qualitative methods with descriptive analysis techniques. The results of the research show that there are several writing errors that often occur in study tour reports for middle school and high school/vocational school students, namely errors in the use of capital letters, errors in the use of non-standard words, errors in the use of punctuation marks, and errors in the use of inappropriate words. The level of writing errors in.